The Fallen Angel : Gabriel Allon #12 - Silva, Daniel, 1960- (New York : HarperCollins, 2012)
When a body is found beneath Michelangelo's dome, Gabriel Allon is summoned to secretly investigate the death that has been ruled a suicide--a case that brings about an unthinkable act of sabotage.
Keywords: Murder -- Fiction; Homicide -- Fiction; Mystery fiction